The Church of the Virgin Hodigitria and its Images Drawn on Olonets City Plans of the 17th–18th Centuries - Milchik, Mikhail I. (Actual Problems of Theory and History of Art, 2016)
The building contract between the church community and the carpenters’ artel for the construction of a wooden church near a fortress in the town of Olonets is a unique document. Firstly, it contains the construction plan on the reverse. Secondly, there are a few depictions of this church taken from different visual angles in the Olonets city plan drawings that date to the second half of the 1690s and 1702 (a new stonewall church was erected in 1752). As a result, we have an opportunity to compare a verbal description with the embodiment and with other cribwork churches of the same period, and thus to make a justified reconstruction of the object of our research. Unscaled construction projects dating to the second half of the17th century are very rare for Russia and usually apply only to stone structures.
Keywords: building contract; cribwork church; drawing plan; porch gallery; rounded (pentahedral) altar prirub; stoop; locker; bell tower